The Problematics of Islamic Religious Education Teacher In Using of Instructional Media at SD Negeri 06 Pancung Soal Pesisir Selatan - Alfurqan Alfurqan; M Tamrin; Zulvia Trinova; Zuhdiyah Zuhdiyah (AT-TA'LIM, 2019)
The purpose of this study is to describe the condition of PAI teachers in teaching related to the use of instructional media. This study uses a qualitative approach. The instrument of this research is the researcher himself. Key informants are PAI teachers, while supporting informants are principals, teachers and students as well as other informants who are obtained by using snow-ball sampling.The findingsof the study obtained an overview of the conditions of theimplementation of the process of religious learning conducted by the teacher. In this case therelationship with variations in using instructional media. It was found in this study that in generalthe teaching teacher was accustomed to traditional ways and could not use the media. Besidesthat, the instructional media available in schools cannot be used for various reasons. And eventeachers have been satisfied with the teaching conditions that have been carried out for years,so they are not interested in using the right instructional media in accordance with the learningmaterial provided.